Determinan Terpilih untuk Kualitas Air Embung pada Lahan Tadah Hujan di Karanganyar, Jawa Tengah - Achmad Adi Surya Sustama; Komariah Komariah; Arwa Farida Lukito; Sumani Sumani; Dwi Priyo Ariyanto; Widyatmani Sih Dewi (Institut Pertanian Bogor, 2023)
Water conservation is needed to overcome the shortage of irrigation water through harvesting rainwater on rainfed land using small farm reservoir. Intensive agricultural activities cause a reduction in land resources which disrupts hydrological functions (water quantity and quality). This study aims to determine the selected parameters for small farm reservoir water quality and identify water quality based on irrigation water standards according to FAO (1994) and PP No. 82 of 2001. The research was conducted from March to December 2014 in Karanganyar Regency, Central Java Province. This study used a descriptive exploratory survey method with purposive sampling. Water quality data was analyzed using Principal Components Analysis (Multivariate Test) MINITAB 16 to determine the main components as the selected determinants. Furthermore, based on the results of the PCA analysis, 5 variables were obtained whose eigenvalue proportions met the main criteria, including DHL of 0.467; SAR of 0.542; pH of 0.538; Actual Savings Ratio (ASR) of 0.662; and water-air temperature deviation of 0.612. Furthermore, a match is made between the selected determinant measurement data and the water quality standard. The results of matching to the selected determinants for water quality in the reservoir have met the water quality standards for irrigation based on FAO (1994) and Government Regulation no. 82 (2001). The soil characteristics of the catchment area also affect water quality because in rainwater harvesting, surface runoff in the catchment area will flow and be accommodated by the small farm reservoir. Keywords: water quality, small farm reservoir, PCA, water conservation, rainfall harvesting